The Cultural and Religious Impacts of Arabic Language on the State and Citizens: Bangladesh as a Case Study - Abu Al-Kalam, Muhammad (Journal of Humanities & Social Sciences, 2025)
This study examines the cultural and religious impacts of the Arabic language on the state and citizens of Bangladesh, considering it a sacred language in Islam and one of the influential factors in shaping the religious and cultural identity of the Bangladeshi people. The research aims to reveal the role of the Arabic language in strengthening Islamic affiliation, consolidating religious values, and influencing the fields of education, culture, politics, and religion, with a particular focus on how this influence is reflected in the behavior of individuals and the institutions of the state. The researcher adopted the descriptive-analytical method, analyzing historical, educational, and cultural texts and sources, in addition to the views of several Bangladeshi and Arab scholars and thinkers regarding the presence of the Arabic language in Bangladeshi society and its educational and religious institutions. The findings revealed that the Arabic language constitutes a central element in shaping the Islamic identity of Bangladeshi society, as it is the language of the Qur’an and religious rituals. It also contributes to strengthening spiritual and cultural ties between Bangladesh and the broader Islamic world. Moreover, the spread of Arabic and Islamic schools, along with the growing interest in learning Arabic in universities and religious institutions, has helped to promote religious awareness and enhance cultural and civilizational communication. Finally, the study concluded that the Arabic language is not merely a medium of religious expression but an active tool in building the moral and intellectual values of citizens. Supporting it and expanding its presence in education, media, and cultural policies would contribute to consolidating Islamic identity and promoting national unity within the framework of Bangladesh’s cultural diversity.